Trace elements in subantarctic false killer whale (Pseudorca crassidens) tissues, including the skin as an offshore bioindicator - Cáceres Saez, Iris; Haro, Daniela; Blank, Olivia; Aguayo Lobo, Anelio; Dougnac, Catherine; Arredondo, Cristóbal; Cappozzo, Humberto Luis; Ribeiro Guevara, Sergio (Environmental Science and Pollution Research)
On a global scale, cetaceans are recognized well indicators of marine ecosystem health. Trace elements accumulate in their bodies and potentially constitute a toxicological threat. Here, the concentrations of essential Se; unknown physiological elements Br, Rb, Cs, Ni, and Sr; and pollutants arsenic, Cd, Hg, and Ag were assessed in the skin of false killer whales (Pseudorca crassidens) stranded at Estrecho de Magallanes, South America, and next, tissue comparisons and relationships between elemental concentrations in the skin and internal tissues (liver, kidney, spleen, lung, skeletal muscle, and testis) were assessed. Results showed elemental concentration variations among tissues. Selenium concentration was found to be higher in the liver 398 (75) μg g−1 dry weight (DW) (standard deviation in parenthesis), followed by skin. Rubidium and Br concentrations were higher in testis 7.92 (0.42) and 99.1 (5.4) μg g−1 DW, respectively, and Cs in muscle 0.36 (0.12) μg g−1 DW, while Ni concentrations range (<0.05–0.91 μg g−1 DW) did not show differences among tissues. Cadmium and arsenic were found to be higher in kidneys, 71.2 (17.6) and 2.54 (1.77) μg g−1 DW, respectively, while Hg was highest in the liver 1068 (234) μg g−1 DW. Concerning inter-tissue relationships, a positive skin-to-kidney and skin-to-muscle correlations were observed for Cs concentrations, and also Hg showed positive skin-to-spleen, skin-to-kidney, and skin-to-testis correlations, which support its use as potential offshore marine biomonitor. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Haro, Daniela. Universidad Santo Tomas, Santiago; Chile Fil: Blank, Olivia. No especifíca; Fil: Aguayo Lobo, Anelio. Instituto Antártico Chileno; Chile Fil: Dougnac, Catherine. Wildlife Conservation Society; Chile Fil: Arredondo, Cristóbal. Wildlife Conservation Society; Chile ...